Sexual offender treatment for reducing recidivism among convicted sex offenders: a systematic review and meta-analysis - Schmucker, Martin (Campbell Systematic Reviews, 2017)
Sexual offender treatment programs to reduce reoffending have been implemented in many countries as part of a strategy in managing this offender group. However, there are still controversies regarding their effectiveness